2019
DOI: 10.1007/s00436-019-06388-6
|View full text |Cite
|
Sign up to set email alerts
|

Serological and molecular investigation of selected parasitic pathogens in European brown hare (Lepus europaeus) in Greece: inferring the ecological niche of Toxoplasma gondii and Leishmania infantum in hares

Abstract: The occurrence of infection or exposure to Toxoplasma gondii, Neospora caninum, and Leishmania infantum was investigated in European brown hares (Lepus europaeus, EBH) hunter-harvested over two consecutive hunting seasons in northern and central Greece. Geographical information system was used along with the ecological niche model to define the geographical distribution of seropositive hares relative to environmental parameters and to identify high-risk areas for hare exposure. Molecular analysis showed that 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Akohundi et al, (2016) identified 53 different species of the Leishmania genera and more than 800 vectors capable of transmitting the infection stadium of the parasite (promastigote) to the host [ 6 ]. Although domestic dogs are the definitive hosts, different studies have documented L. infantum in other mammalian species, including horses, cats, pigs, wild rodents, hares, wild canids, and humans [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The host immunity response determines the infection severity of L. infantum , which can be mild, moderate, severe, or very severe [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Akohundi et al, (2016) identified 53 different species of the Leishmania genera and more than 800 vectors capable of transmitting the infection stadium of the parasite (promastigote) to the host [ 6 ]. Although domestic dogs are the definitive hosts, different studies have documented L. infantum in other mammalian species, including horses, cats, pigs, wild rodents, hares, wild canids, and humans [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The host immunity response determines the infection severity of L. infantum , which can be mild, moderate, severe, or very severe [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding lagomorphs, the L. infantum DNA prevalence in European brown hares ( Lepus europaeus ) originating from Northern Greece was reported to be 23.49% during 2007–2011, and the subsequent phylogenetic analysis revealed that all sequences belonged to the L. donovani complex [ 73 ]. Likewise, a later study in hares sampled in Northern Greece showed a L. infantum DNA prevalence of 20%, while a lower percentage of PCR-positive animals (7.4%) was recorded in Central Greece [ 74 ]. A total seroprevalence of 12.4% was reported in the same hare population [ 74 ].…”
Section: Prevalence Of L Infantum In Other Host Po...mentioning
confidence: 99%
“…Likewise, a later study in hares sampled in Northern Greece showed a L. infantum DNA prevalence of 20%, while a lower percentage of PCR-positive animals (7.4%) was recorded in Central Greece [ 74 ]. A total seroprevalence of 12.4% was reported in the same hare population [ 74 ]. Both studies identified precipitation seasonality as a critical influential environmental parameter associated with L. infantum infection in hares, probably due to its effects on the sandfly vector activity, survival, and oviposition sites [ 73 , 74 ].…”
Section: Prevalence Of L Infantum In Other Host Po...mentioning
confidence: 99%
See 1 more Smart Citation
“…In several European countries, the prevalence of T. gondii was tested with different serological methods such as MAT, IFAT, ELISA, DAT and SFDT (45)(46)(47)(48). The results in the Brown hare (Lepus Europaeus) were reported in different rates such as, 5.7% in Greece (45), 6% in Slovakia (46), 9% in France (47), 13% in Austria, 21% in the Czech Republic (46) and 46% in Germany (36), while no seropositivity was detected in Sweden (48). In the present study, when compared with the results of other countries, the low seropositivity rate of T. gondii (4.8%) was found similar to the prevalence rates which were found in Greece and Slovakia.…”
Section: Encephalitozoon Cunculi Francisella Tularensis Toxoplasma Gondiimentioning
confidence: 99%